KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IX SMP NEGERI 2 GALESONG SELATAN BERDASARKAN LANGKAH POLYA - Musdalifah; Tiwi Saputriani; Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This descriptive qualitative research aimed to analyze the mathematical problem-solving abilities of 32 students in class IX A of SMP Negeri 2 Galesong Selatan, specifically when solving System of Linear Equations in Two Variables (SPLDV) word problems. The evaluation framework was based on Polya's four steps (understanding the problem, devising a plan, carrying out the plan, and looking back). Through tests and interviews, students were categorized into three groups: students with high ability successfully completed all four Polya steps accurately; students with moderate ability typically managed to complete only three steps and showed weakness in the crucial looking back stage; and students with low ability often only managed to understand the problem or entirely failed to formulate a solution plan. The analysis ultimately revealed a significant weakness in students' capabilities at the planning, execution, and especially the looking back stages. Therefore, the study recommends that these abilities be improved through regular practice with non-routine problems that specifically emphasize the systematic application of Polya's steps.